Pengaruh Intervensi Edukasi Kesehatan Secara Daring terhadap Pengetahuan Bahaya Rokok Masyarakat Indonesia Usia 20-40 - Felicia Lidya Kong; Vito Damay; Dyah Novita Anggraini (Syntax Corporation Indonesia, 2021)
Based on data from the World Health Organization, more than 8 million of the population died due to tobacco use globally. Around 90% of them died as a result of direct use, while 10% were exposed by other people. There are 225.700 people killed by tobacco exposure and tobacco-related disease in Indonesia each year. This research was conducted to consider efforts to reduce the level of cigarette consumption through health education about the dangers of smoking. The method used was a one-group pretest–posttest design. A total of 108 people participated in the webinar and completed questionnaires before and after the intervention to assess their level of knowledge about the dangers of smoking. The findings revealed a difference in the mean level of knowledge among respondents before and after the webinar, with pre-test score of 149.07 and post-test score of 157.78 out of 170 as the total score. There were significant differences (p < 0.001), implying that the health education intervention was effective in increasing knowledge about the dangers of smoking among Indonesians aged 20-40 years